Evaluasi dan Perbaikan Tampilan Website Masterprima menggunakan Pendekatan Human-Centered Design (HCD) - Hanif Naufal Ashari; Hanifah Muslimah Az-Zahra; Kariyoto Kariyoto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Lembaga Bimbingan Belajar Masterprima is a company engaged in the educational field that has a website to help students or the public who want to find information about tutoring easily. However, this website has several problems, like the inconsistent content layout and the arrangement of tryout score information is too tight and small. The study includes evaluation and improvement of existing problems using the Human-Centered Design (HCD) approach. This study aims to produce a design solution that meets the aspects of usability learnability, efficiency, error, and satisfaction by using the help of the Indonesian Computer System Usability Questionnaire (CSUQ). In the initial test, the learnability value was 72.2%, efficiency was 51.1%, satisfaction was 76%, and error was 22.2%. The results become a reference for making design solutions that can improve the usability score of the website. The design solution then tested in the final test and obtain an increase in the value of learnability by 16.7%, efficiency by 33.2%, satisfaction by 7%, and a decrease in error value by 12.5%. From the comparison results of the initial and final tests, it is known that the design solution has succeeded in increasing the usability value of the Masterprima website.